Inhibitory Effects of Alendronate on Adhesion and Viability of Preosteoblast Cells on Titanium Discs - Lilakhunakon, Charukrit; Suwanpateeb, Jintamai; Patntirapong, Somying (European Journal of Dentistry, 2021)
Objective This study aimed to investigate the effects of alendronate (ALN; a bisphosphonate) on adhesion and viability of preosteoblasts using different cell passages on sandblasted and acid-etched (SLA) Ti surfaces.Materials and Methods Preosteoblast, MC3T3, cells (passage 42; P42 and passage 62; P62) were cultured with ALN (1 and 5 µM) on cell culture plate for 7 days. Cells were lifted, counted, and seeded on SLA Ti surfaces. Cells were incubated on the discs for 6 hours to examine cell adhesion by using confocal microscopy and for 24 hours to determine cell viability by using MTT assay.Results ALN interfered with cell adhesion on Ti surfaces by reducing the cell number in both cell passages. Nuclei of untreated cells showed oval shape, whereas some nuclei of ALN-treated cells demonstrated crescent and condensed appearance. ALN at 1 and 5 µM significantly decreased nuclear area and perimeter in P42, while ALN at 5 µM reduced nuclear area and perimeter in P62. After 24 hours, cells (P42) grown on Ti surfaces showed decreased cell viability when culturing with 5 µM ALN.Conclusion ALN reduced cell adhesion and viability of preosteoblasts on Ti surfaces. ALN treatment seemed to exert higher inhibitory effects on nuclear shape and size as well as cell viability in lower cell passage. This led to the reduction in cell to implant surface interaction after encountering bisphosphonate treatment.
Keywords: bisphosphonate; implant; osteoblast; cell adhesion; cell viability